Symmetric supercapacitor with supercapattery behavior based on carbonized iron cations adsorbed onto polyaniline. (1st February 2018) - Rantho, M.N.; Madito, M.J.; Manyala, N.
Abstract: The electrode material based on the carbonization of Fe cations adsorbed onto polyaniline (PANI) (C-Fe/PANI) was directly synthesized on nickel foam by pyrolysis of the iron-PANI mixture coated on nickel foam in a tube furnace under the N2 atmosphere. The characterization of the as-synthesized electrode materials was carried out using X-ray diffraction (XRD), Raman spectroscopy, Fourier transform infrared (FT-IR) spectroscopy, scanning electron microscopy (SEM), high-resolution transmission electron microscopy (HR-TEM) equipped with a scanning transmission electron microscopy along with energy dispersive X-ray (STEM-EDX) and X-ray photoelectron spectroscopy (XPS). The electrochemical behavior of the working electrode was analyzed in both positive and negative potential window in a three-electrode cell configuration using 6 M KOH electrolyte, and thereafter, a C-Fe/PANI symmetric device was successfully fabricated. The C-Fe/PANI symmetric device was found to perform at a high applied potential difference of 1.65 V in 6 M KOH. At a current density of 0.5 A g −1, this device exhibited energy and power densities of 41.3 W h kg −1 and 231.9 W kg −1 respectively. Additionally, the device exhibited a maximum power of 469.4 kW kg −1 . The device further showed excellent cycling stability with 100% Columbic efficiency and capacity retention of 72% at a current density of 5 A g −1 over 10 000 galvanostatic charge-discharge cycles. Graphical abstract: Image 1 Highlights: C-Fe/PANI was synthesized on nickel foam by pyrolysis of the iron-PANI mixture. The symmetric device was fabricated using C-Fe/PANI electrode. The symmetric device exhibited high energy density and good long-term stability.